2011
DOI: 10.1111/j.1600-0412.2011.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtle perturbations of genital microflora alter mucosal immunity among low-risk pregnant women

Abstract: Objective Alteration in the vaginal flora has been associated with adverse pregnancy outcomes. The objective of this study was to examine the impact of changes in individual microflora on genital immunity among low-risk pregnant women in early pregnancy. Design Cross-sectional study. Setting Large, tertiary care, academic hospital clinic. Population Low-risk women were enrolled prior to 14 weeks’ gestation. Methods Women were included if they had no medical or previous obstetrical complications, were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
20
0
3
Order By: Relevance
“…Slight changes in the microbial composition of the vaginal flora were already demonstrated to influence the local cytokine production 38. Nevertheless, no trend to increases on the levels of cytokine was found in relation to the participation of A vaginae , Megasphaera sp.…”
Section: Discussionmentioning
confidence: 95%
“…Slight changes in the microbial composition of the vaginal flora were already demonstrated to influence the local cytokine production 38. Nevertheless, no trend to increases on the levels of cytokine was found in relation to the participation of A vaginae , Megasphaera sp.…”
Section: Discussionmentioning
confidence: 95%
“…with lower levels of genital HIV-1 RNA. 21 Gardnerella vaginalis has been associated with higher concentrations of vaginal interleukin (IL)-1b 26,27 and Lactobacillus spp. with lower concentrations of IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…There also exists evidence that inflammation plays an important role in dysbiosis-induced cervical disease. Clinical studies have shown that levels of vaginal proinflammatory cytokines are higher in women with dysbiosis [69, 70] which can result in chronic inflammation; a well-known factor in carcinogenesis of numerous tissues in the body [97]. …”
Section: Potential Mechanisms Of Vaginal Microbiota-mediated Cervicalmentioning
confidence: 99%